Refresentation Of Criminal Case Settlement Outside The Court Using Larvul Ngabal Customary Law In Southeast Maluku District - Fauziah Rahawarin (IHSA Institute, 2023)
Research on Lavrul Ngabal's customary law was carried out for the sake of developing legal and criminal knowledge which the Kei community considers to be quite an effective customary law norm. The purpose of this research is to represent the way of resolving criminal cases outside the court using customary law of Lavrul Ngabal as an effort to prevent and control crimes such as immoral acts. There are two sources of research data, namely primary data and secondary data. The primary data was obtained through interviews and observations, while the secondary data was obtained through a documentation study. The location of this research was conducted in Southeast Maluku Regency. The results of this study indicate that. Settlement of criminal cases outside the court using the customary law of Larvul Ngabal in Southeast Maluku Regency is through customary criminal justice carried out in the form of mediation (sdov: negotiations) involving kings, the parties involved, and clan heads. Traditional leaders in carrying out their functions as mediators, in practice traditional leaders generally use this approach together, especially in resolving private and public disputes